PENGARUH STRUKTUR KEUANGAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN MEDIASI: STRUKTUR MODAL - Sayekti, Neny Winda; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out whether the capital structure is able to mediate the correlation betweenfinancial structure and investment decision to the firm value in LQ45 Companies which are listed in IndonesiaStock Exchange Indonesia. This research is a quantitative research. The population is all companies which arelisted in LQ-45 index in Indonesia Stock Exchange Indonesia in 2013-2015 periods, the sample collectiontechnique has been carried out by using purposive sampling so that 26 companies from various sector in LQ-45index have been selected as samples. In this research the measurement of assets structure is used to compare fixedassets with the total assets, the firm size has been done by using log assets, capital structure which has been doneby using DER and the firm value has been done by using PBV. Based on the result of hypothesis test, it can beconcluded that assets structure give positive influence to the firm value; firm size give negative influence to thefirm value meanwhile the investment decision does not give any influence to the firm value. Capital structure asintervening variable does not give any influence to correlation between investment decisions to the firmcompany.Keywords: Asset structure, firm size, investment decision, capital structure firm value.